Contemporary Topics in Patient Safety Volume 1 - Stawicki, Stanislaw P.; Firstenberg, Michael S. (IntechOpen, 2022)
As healthcare systems continue to evolve, it is clear that providing safe, high-quality care to patients is an extremely complex process. Ranging from multi-disciplinary teams to bedside care, virtually every aspect of the patient-care experience provides us with an opportunity for doing things better, from improving efficiency, safety, and overall outcomes to reducing costs and promoting team synergy. This book, the fifth in our patient safety series collection, consists of chapters that help explore key concepts related to both the safety and quality of care. In a departure from the vignette-driven format of our earlier books, this installment gravitates toward discussing frameworks, theoretical considerations, team-centric approaches, and a variety of other concepts that are critical to both our understanding and the implementation of safer and better-performing health systems. We also feel that the knowledge presented herein increasingly applies across the world, especially as global health systems evolve and mature over time. It is our goal to improve the recognition of potential opportunities that will highlight various aspects of the delivery of healthcare and thus contribute to better patient experiences, with safety at the forefront. Topics covered in this volume, as well as the previous volumes, highlight the critical importance of identifying and addressing opportunities for improvement, not as one-time events, but rather as continuous, hardwired institutional processes.